Small States and Large Weak States in the Eurovision Song Contest. Gaining Soft Power and Asserting Identity - Hera Melgar Aðalheiðardóttir 1993- (2022)
This thesis explores whether, and then how, small states and large weak states use the Eurovision Song Contest to gain soft power and status internationally. Large weak states and small states have well founded, but at the same time different reasons for wanting to use Eurovision to exalt their image as they often lack opportunities to prove themselves on the international stage. This is a comparative case study that looks at the cases of four countries; Estonia, Iceland, Russia and Ukraine, in the context of small state studies. The four countries’ conduct and behaviour in Eurovision is examined and put in context with their history, in order to be able to better explain the motives of these countries for using Eurovision to gain soft power and status. The findings emphasise the latent political significance of the Eurovision Song Contest, and more specifically, the different ways through which countries can use the contest for political purposes. The study concludes that Estonia, Iceland and Ukraine have all used Eurovision as a platform for nation branding, status and soft power seeking internationally as well as nationally, while Russia has only used the contest to gain status and soft power abroad and not at national level. The contest has played an important role in the reconstruction of Estonia’s and Ukraine’s national identity and their integration into western European culture. According to the findings, it can be stated that the size of the countries is not a defining factor in the context of this research, but rather their potentiality and how they are perceived in the international community, that defines their status as weak states.